Ejercicios prácticos para la inclusión financiera de las mujeres - Paez, Ana Maria; Derenoncourt, Marie Ena (2023)
The presentation focuses on applying key concepts on women's financial inclusion and how to design gender-sensitive interviews and field interventions in climate risk management.